Gene-Environmental Interactions as Metabolic Drivers of Nonalcoholic Steatohepatitis - Albhaisi, Somaya; Sanyal, Arun J. (Frontiers in Endocrinology, 2021)
Nonalcoholic fatty liver disease (NAFLD) has emerged as a leading cause of chronic liver disease worldwide in the past few decades as a consequence of the global obesity epidemic and is associated with significant morbidity and mortality. NAFLD is closely associated with components of the metabolic syndrome, type 2 diabetes mellitus and cardiovascular disease, suggesting a plausible metabolic mechanistic basis. Metabolic inflexibility is considered a nidus for NAFLD pathogenesis, causing lipotoxicity, mitochondrial dysfunction and cellular stress leading to inflammation, apoptosis and fibrogenesis, thus mediating disease progression into nonalcoholic steatohepatitis (NASH) and ultimately cirrhosis. In this review, we describe they key metabolic drivers that contribute to development of NAFLD and NASH, and we explain how NASH is a metabolic disease. Understanding the metabolic basis of NASH is crucial for the prevention and treatment of this disease.